Shortlisted Biennial of Design and Poster Bolivia BICeBé - Panayides, Angelos (My University, 2026)
The Biennial of Design and Poster Bolivia BICeBé hereby awards this certificate in recognition of being shortlisted among 481 posters to be part of the Main Exhibition of BICeBé 2025. The International Poster Call received 12,648 submissions from 91 countries worldwide.
Keywords: Arts and entertainment